Insulin therapy for hyperglycemia in critically ill patients - Julianti Julianti; Silvia Triratna; Aditiawati Aditiawati; Irfanuddin Irfanuddin (Indonesian Pediatric Society, 2013)
Background Hyperglycemia in critically ill patients is associated with higher mortality. Insulin therapy may improve outcomes, not only by preventing deleterious effects of hyperglycemia, but by improving the molecular dynamics in organ dysfunction.Objectives To assess the effects of insulin therapy on critically ill patients in an intensive care unit (ICU) setting and the risk of hypoglycemia.Methods An open-label, clinical trial was conducted in the Pediatric Intensive Care Unit (PICU) of Dr. Moh. Hoesin Hospital, Palembang, from November 2011 to March 2012. Subjects were consecutively assigned to receive either regular insulin at a dose of 0.05 U/kg/h if the blood glucose level reached >200 mg%, or standard therapy (control group). Blood glucose levels were measured hourly until they reached 80-110 mg%. Dose adjustments were made when the blood glucose level reached 145 mg%, by reducing the insulin dose to 0.025 U/kg/h. Outcomes of therapy were measured by Pediatric Logistic Organ Dysfunction (PELOD) score improvement, mortality rate and the occurrence of hypoglycemia.Results Forty subjects were enrolled in this study, with 20 subjects assigned to the insulin therapy group and 20 subjects to the standard therapy group. Two subjects, one from each group, were not included in the final analysis due to their deaths within 24 hours. There was no significant difference in distribution of PELOD scores before intervention between the groups (OR=0.5; 95%CI 0.1 to 1.9, P=0.32). However, after intervention, the PELOD scores was significantly lower in insulin therapy group compared to control group (OR 0.2; 95% CI 0.05 to 0.8, P=0.02). In the insulin group after intervention, fewer subjects had scores >20.5 and more subjects had scores â‰¤20.5, indicated a lower risk of organ dysfunction. There was also a significantly lower mortality rate in the insulin group compared to the control group (OR 0.2; 95% CI 0.05 to 0.8, P=0.02). None of the subjects suffered hypoglycemia.Conclusion Insulin is beneficial in improving organ dysfunction and decreasing mortality for critically ill patients.